(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The relevance of the chosen topic is due to the fact that this article discusses some types of modern innovative technologies. Innovative technology develops day after day and poses great challenges that can be solved during the training of students.